Health as the Main Value of Life in the Well-Wishes of the Mongolian peoples - Evdokia E. Khabunova; Ludmila S. Dampilova; Balzira V. Elbikova (Монголоведение)
Introduction. The article deals with traditional good wishes of Mongolian peoples (Buryat: yurol, ureel; Kalm.: yeral; Mong.: yerol; Xinjiang-Oirat.: yeral) as an admonition about the importance of good health to ensure a long, full, productive and happy human life. This theme belongs to the poorly studied problems, despite the fact that the motif of health permeates all genres of folklore of Mongolian peoples. The importance of the studied problem is obvious in the context of actualization of healthy lifestyle in modern conditions. The aim of the study is to determine the nature of the implementation of the motif “health” in well-wishes of Buryats, Kalmyks, Mongols and Xinjiang Oirats, to consider the basis of general formulas — wishes aimed at ensuring strong health to a person from the moment of his birth, at his speedy and painless socialization, at his ability to work and usefulness for the family, clan and state. Matherials and Methods. The study is based on the materials identified from oral sources during the expedition work and from publications containing the texts of traditional good wishes. When analyzing the national texts of well-wishes, a combination of elements of different methods (comparative-historical, comparative-typological, elements of pragmatic analysis, etc.) is used, which are important for studying the nature of representation of health wishes in the folklore tradition of related peoples (Buryats, Kalmyks, Mongols and Xinjiang Oirats) separated in time and space. Results. In the process of comparative study of the national texts of well-wishes it was established that the wish for health is the most widespread and stable form of greeting, which accompanies human life from the very moment of birth. The nomads’ idea of a healthy person is equated with the notions of: “strong”, “full-fledged”, “full member of society”, “normal person”, “happy person”, “prosperous person” “long-lived person”, “useful person”, “steadfast”, “reliable”. Manifestation of these health criteria are characterized by constancy in many well-wishes, which is confirmed by textual coincidences of poetic formulas.